Randomized consensus with regular registers - Hadzilacos, Vassos; Hu, Xing; Toueg, Sam (Information processing letters, 2022)
•The randomized consensus algorithm of Aspnes and Herlihy, which was shown to work with atomic registers, works even with regular registers.•This result shows that this algorithm works if the atomic registers that it uses are replaced with linearizable register implementations.•This is perhaps surprising because it is known that randomized consensus algorithms may require strongly linearizable registers to work. The well-known randomized consensus algorithm by Aspnes and Herlihy (1990) for asynchronous shared-memory systems was proved to work, even against a strong adversary, under the assumption that the registers that it uses are atomic. With atomic registers every read or write operation is instantaneous (and thus indivisible). As pointed out by Golab, Higham, and Woelfel (2011), however, a randomized algorithm that works with atomic registers does not necessarily work if we replace the atomic registers that it uses with linearizable implementations of registers. This raises the following question: does the randomized consensus algorithm by Aspnes and Herlihy still work against a strong adversary if we replace its atomic registers with linearizable registers? We show that the answer is affirmative; in fact we show that even linearizable registers are not necessary. More precisely, we prove that the algorithm by Aspnes and Herlihy works against a strong adversary even if the algorithm uses only regular registers.